Faktor-Faktor yang Mempengaruhi Niat Perilaku Pengguna BSB Mobile Banking di Kota Palembang - Igustisari, Cindy; Rosa Indah , Dwi; Eka Sevtiyuni, Putri (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
In the era of globalization, the use of the internet and technology has become commonplace. One of them is the banking sector, which has shifted to offering services with a digital touch, such as mobile banking. Rating assessment on Playstore, the BSB Mobile application received a score of 4.0. When using m-banking, customers found complaints such as user accounts being blocked for no reason, transactions failing but balance deductions still occurring, errors or bugs in the application. These complaints will reduce the user's desire to use the application. Researchers applied the UTAUT2 method and added Trust and Perceived Risk variables to analyze what factors influence BSB Mobile user intentions. The results of this analysis found that the variables Social Influence and Hedonic Motivation influence Intentional Behavior, while the variables Performance Expectations, Business Expectations, Facilitating Conditions, Price Value, Habits, Trust, and Perceived Risk do not influence the Intentional Behavior of BSB Mobile banking users.